Strand 1: Learning Community On-Line: Developing Shared Spaces in the Academic Context - Graebner, Celia (Proceedings of the International Conference on Networked Learning, 1998)
It is generally cited as the key advantage of a virtual learning institution that it is time and space independent. And, to date, the dominant environment for academic learning on-line has been asynchronous (e-mail, discussion lists, and computer-mediated conferencing) Counter to this, discourse around the virtual community as a type of the post-modern community draws on continuities with traditional understandings of community as defined by location and time, and in particular emphasizes the appropriation and domestication of notional on-line spaces through the evolution of local cultures and conventions. This paper approaches the concept and practice of an on-line learning community as an intersection of these two perspectives, and also as a site of tension between them. The main case study from which illustrations are drawn is a six-month period covering the establishment of an on-line collaborative learning group. The context was an award-bearing professional development course and the environment asynchronous conferencing (primarily LotUS Notes, bur the outcomes and method are not closely software dependent.) It is hoped that the conference session can be fairly interactive, using the broad framework of analysis laid here to discuss more detailed examples of community-building interaction.